2021
DOI: 10.1177/02676591211001782
|View full text |Cite
|
Sign up to set email alerts
|

Central venoarterial extracorporeal life support in pediatric refractory septic shock: a single center experience

Abstract: Objective: Venoarterial extracorporeal membrane oxygenation (VA ECMO) is recognized as a potential support therapy for pediatric patients with refractory septic shock (RSS). This review aims to report our experience with central VA cannulation in pediatric patients with RSS, and to compare this with peripheral VA ECMO cannulations for this condition at our institution. Design: Retrospective case series. Setting: Pediatric and cardiac intensive care units in an academic pediatric hospital. Patients: All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The inconsistent data still exist. 52 , 54 , 55 , 56 , 57 , 58 , 59 In a study with 777 children who received VA‐ECMO support for heart diseases, Merrill et al 52 found that patients were older (median age, 0.64 versus 0.10 years) and patient weight was greater (median weight, 7.0 kg versus 4.0 kg) in survivors compared with nonsurvivors. By univariate and multivariate analyses, it similarly indicated that older or overweight children had a better chance of surviving to hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistent data still exist. 52 , 54 , 55 , 56 , 57 , 58 , 59 In a study with 777 children who received VA‐ECMO support for heart diseases, Merrill et al 52 found that patients were older (median age, 0.64 versus 0.10 years) and patient weight was greater (median weight, 7.0 kg versus 4.0 kg) in survivors compared with nonsurvivors. By univariate and multivariate analyses, it similarly indicated that older or overweight children had a better chance of surviving to hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent single‐center study on VA‐ECMO support for refractory septic shock in children reported a survival rate of 66.7% in central cannulation patients compared with 40% in patients receiving peripheral cannulation. 59 Early central cannulation providing adequate hemodynamic support before more severe and potentially irreversible organ dysfunction develops may contribute to better outcomes. However, we found central cannulation was associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Central cannulation is commonly used in patients with recent sternotomy as it allows quick access to the right atrial appendage and the ascending aorta. Central cannulation has shown some benefit in pediatric patients in septic shock as this allows larger cannulas to be placed, allowing higher flow rates [ 16 18 ]. Although ECMO provides right and left ventricular support in patients with biventricular circulation, it does not provide active decompression of the left ventricle.…”
Section: Veno-arterial Ecmomentioning
confidence: 99%
“…An assessment of the funnel plots of all the patients is shown in Figure 3. The 14 studies included in the systemic review and meta-analysis that reported on children with refractory septic shock requiring ECMO are shown in Table 1 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). And the details of the cohort studies are summarized in Table 2.…”
Section: Clinical Outcomesmentioning
confidence: 99%